Pengaruh Earning Per Share dan Return On Asset terhadap Harga Saham Pada PT Surya Citra Media TBK periode 2014-2023 - Suraya, Amthy; Riyanto, Andy (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The purpose of this research is to analyze the influence of Earning Per Share and Return On Assets on Stock Price at PT Surya Citra Media Tbk in 2014-2023. This Research is a type of quantitative research using descriptive analysis methods and using data on financial statements in the form of balance sheets and income statement PT Surya Citra Media Tbk. Based on the results of the study showed that patially Earning Per Share and Return On Asset had a significant effect on the stock price in PT Surya Citra Media Tbk. in 2014-2023. Then simultaneously it is known that Earning Per Share and Return On Assets have a significant effect on stock price in PT Surya Citra Media Tbk. in 2014-2023.